CLINICAL AND PSYCHOLOGICAL SUBSTANTIATIONS OF INDICATIONS FOR ORAL CAVITY SANATION IN CHILDREN OF DIFFERENT AGES UNDER GENERAL ANESTHESIA - О. Prokhno; P. Koval (Bukovynian State Medical University, 2019)
This article presents clinical and psychological substantiations of indications for oral cavity sanation in children of different ages under general anesthesia based on the assessment of dental status and child's psychological characteristics at different ages, such as intellectual development, temperament and phobias.